Association between miR-365 polymorphism and ischemic stroke in a Chinese population - Weng, Yin-Hua; Yu, Wen-Tao; Luo, Yan-Ping; Liu, Chao; Gu, Xi-Xi; Chen, Huo-Ying; Liu, Hong-Bo (Frontiers in Neurology, 2023)
Ischemic stroke (IS) represents a major cause of morbidity and mortality across the globe. Aberrant expression of miR-365 has been found to be implicated in a wide array of human diseases, including atherosclerosis and cancer. Studies on single-nucleotide polymorphisms (SNPs) in miRNA genes can help gain insight into the susceptibility to the condition. This study aimed to examine the relationship between miR-365 SNPs and the risk of IS. The study recruited 215 IS patients and 220 controls. The SNPscan genotyping was employed to genotype three polymorphic loci (rs121224, rs30230, and rs178553) of miR-365. The relative expression of miR-365 in peripheral blood mononuclear cells of the patients and controls was determined by using real-time quantitative PCR. The miR-365 rs30230 polymorphism exhibited a significant association with the risk of developing IS (TC vs.